Assessment of the relationship between self-esteem and academic score of undergraduate medical students of Azad Kashmir, Pakistan - Arslaan Javaeed; Farah Khan; Nadia Sajjad; Sadia Azam Khan; Sanniya Khan Ghauri (Journal of the Pakistan Medical Association, 2021)
Objective: To assess the relationship between self-esteem and the academic score of undergraduate medical students of Azad Kashmir, Pakistan. Methods: This cross-sectional observational study was performed from June 2018 to June 2019. The study area was Poonch Medical College, Azad Kashmir. The data collection tool was well-verified and widely used Rosenberg self-esteem scale. The study questionnaire was electronically distributed to all Bachelor of Medicine and Surgery students on the Poonch Medical College. The total student was 500 and out of the 253 completed and submitted the questionnaire (response rate of 50.6%). Results: The mean academic score of all students was 66.61 ± 5.42 and the mean RSE score was 28.66 ± 3.98. A statistically significant correlation was not found between age, academic score, and RSE score. Female students had slightly higher academic performance scores and RSE scores compared to the male students, but this difference was not statistically significant. Conclusion: This study did not reveal any significant relationship between academic score and self-esteem of undergraduate medical students. However, both academic scores and self-esteem can be further improved. Future studies are invited to find out the other factors responsible for better academic performance. Keywords: RSE scale, academic performance, medical student, Pakistan Continuous...